CircularEconomy4Colombia Innovation Challenge: Innovations' Booklet - Khader, Taija; Loiseau, Camille (2025)
The CircularEconomy4Colombia Innovation Challenge is an initiative designed to support Colombia’s transition toward a circular economy in the agri-food sector. Through this challenge, we have identified and supported early-stage, high-impact solutions, backed by science and adapted to the local context, that promote efficient resource use, waste reduction, and sustainable development in Colombia.